ZnO‐Reinforced Thermal Regulating Microcapsules with Double‐Layer Shell via Atomic Layer Deposition. Issue 17 (12th May 2022) - Li, Linfeng; Wu, Xi; Zhu, Xiaomeng; Li, Yuanyuan; Zou, Liyi; Wang, Xiuli; Li, Wenbin; Cheng, Xiaomin
Abstract: Conventional plain organic or inorganic shell for microcapsules has their own drawbacks, the organic shell has defects in thermal conductivity and stability; while the compactness and coverage of inorganic shell are not satisfactory. Herein, a novel approach to synthesis of organic–inorganic composite double‐layer shell phase change microcapsule (DLSPCM) is proposed, which is achieved by forming inorganic outer shell on the surface of organic shell via atomic layer deposition (ALD). Taking the pristine microcapsule with paraffin core and melamine formaldehyde (MF) shell as an example, MF‐ZnO composite double‐layer shell (DLS) is formed in this paper. The melting enthalpy of DLSPCM obtained by 100 ALD cycles is 159.7 J g −1, which is only 12.1 J g −1  lower than that of paraffin @ MF microcapsules (control sample), while the thermal conductivity of DLSPCM surges by 77.8%, and the thermal energy storage ability and thermal regulation performance are basically maintained. After 900 thermal cycles, the heat storage capacity of DLSPCM obtained by 100 ALD cycles decreased by only 3%. Besides, the photocatalytic performance and antibacterial activity of ZnO‐reinforced DLSPCM are further confirmed. The successful design of DLSPCM via ALD is prospective for the encapsulation, modification, and reinforcement of phase change microcapsules. Abstract : Organic–inorganic double–layer shell microcapsules (DLSMs) with ZnO outer shell are synthesized by atomic layer deposition. The thermal conductivity and durability of the DLSMs get enhanced, and the thermal energy storage ability and thermal regulating performance are maintained simultaneously. In addition, obtained DLSMs are proved to possess photocatalytic degradation and antibacterial properties based on the characteristics of ZnO.